Propuesta de mejora al Sistema de Gestión de Seguridad y Salud en el Trabajo (SST) de la Universidad Antonio Nariño sede Cartagena de Indias, basado en la ISO 45001 (2023)
Occupational Health and Safety Systems are becoming more and more important within public and private organizations, given that they allow the prevention of occupational accidents and illnesses, to which employees are exposed during their workdays. For this reason, this document is created, the purpose of which was to develop a series of improvements to the Occupational Health and Safety Management System (SST) of the Antonio Nariño University, Cartagena de Indias, in accordance with the provisions of the ISO standard. 45001; whose function allows raising the OSH standard in the UAN, by taking into account a whole series of guidelines and activities, which allow the educational institution to continuously improve its management system called SIGUAN, to prevent accidents, diseases and possible environmental accidents.